# Symbolic logic

Not what you're looking for? Search our solutions OR ask your own Custom question.

Given: f (x) = (x - 3)Â²

g (x) = 2x

x = 5

Find: (a) f Â° g (x)

(b) g Â° f (x)

Â© BrainMass Inc. brainmass.com December 24, 2021, 4:49 pm ad1c9bdddfhttps://brainmass.com/philosophy/logic-critical-thinking/symbolic-logic-function-9797

## SOLUTION This solution is **FREE** courtesy of BrainMass!

f(x)= (x-3)2

g(x)= 2x

where x=5

(g(x))= (2x-3)2

=(2(5)-3)2

=(10-3)2

=(7)2

=49

f (x) ) =2(x-3)2

=2(5-3)2

=2(2)2

=2(4)

=8

https://brainmass.com/philosophy/logic-critical-thinking/symbolic-logic-function-9797